Think with the head and act with the 'heart' - Abd Razak, Dzulkifli (2008)
WHILE the situation in a neighbouring country is deteriorating, Malaysians must be vigilant and ensure that our country doesn't suffer the same fate. There are lessons to be learnt from what is happening there. Already, the common people here are facing challenges to make ends meet. Any disturbances will exacerbate the situation and it must be avoided at all cost. Sectarian and individual ambitions should not take preference over society's wellbeing as this could create even more anxieties and, God forbid, may even lead to violence.